Esthetic smile restoration of anterior teeth by treatment with Ceram.X ® duo: a case report - A. V. Mitronin; A. Sh. Platonova; D. A. Ostanina (Эндодонтия Today)
A female patient, 20 years old, sought care at the dental clinic of Department of Cariesology and Endodontics, MSUMD after an accident, complaining that one of her teeth was broken. Upon clinical examination were diagnosed that the maxillary right central incisor was fractured in the middle-third of the crown, involving enamel and dentin without pulp exposure and without symptoms of concussion and contusion. Treatment options were discussed with a patient; due to a satisfactory amount of coronal tooth available, it was proposed to treat fractured tooth 1.1 with a direct composite restoration by Ceram.X ® duo through the use of diagnostic wax-up and silicone key. During DSD analysis were decided to harmonize the upper smile line by making direct composite build up of teeth 1.2, 2.1, and 2.2.